Current account dynamics and capital mobility in Asian small economies - Sheikh Tareq Selim (Cardiff University, Cardiff Business School, 2006)
This paper explores current account dynamics in eight small economies of Asia to examine whether or not capital flows have been excessive in these countries. Standard assumptions of perfect capital mobility and small open economy are jointly instrumental in simplifying theoretical tractability of many open economy models. In empirical estimations, however, the identification of a small open economy is often oversimplified, which makes celebrated results, such as excessive or too low capital flows in OECD economies, questionable. This paper establishes that the actual extent of capital mobility in small open economies cannot be generally too high or too low. This in turns implies that the general idea of excessive capital flows in small open economies requires revision.
Keywords: 330; Current account dynamics; intertemporal approach; consumption-smoothing; capital mobility